Computational Thinking (CT)-based Student Worksheet to Improve the Mathematical Literacy of Mathematics Prospective Teacher - Swasti Maharani; Vera Dewi Susanti; Tri Andari; Ika Krisdiana; Indra Puji Astuti (AL-ISHLAH: Jurnal Pendidikan, 2023)
Mathematical Literacy ability has important for prospective mathematics teachers. It is closely related to Computational Thinking (CT). The aim of this study is to produce CT-students worksheets to improve the mathematical literacy of prospective mathematics teachers. The development study using model ADDIE (Analysis, Design, Development, Implementation, and Evaluation). Thirty-seven would-be maths teachers participated in the study's sixth semester. Subject criteria are students who are not familiar with CT. The instruments in this study were CT-based student worksheets, validation sheets, student response questionnaires, pre-test and post-test questions. The results showed that CT-based student worksheets met the criteria of valid (validity percentage of 84.5%), practical (practicality percentage of 88.68%), and effective (N-gain value of 46.91%). Based on these results, it's appropriate to conclude that CT-based student papers can help students who want to become math teachers learn more about math. Recommendations for further research can be made on the development of a wider material and a wider subject as well.